Antibacterial Activity Test Of Extract And Fraction Of N-Hexane, Ethyl Acetate And Water Of Pineapple Peel (Ananas Comosus (L.) Merr.) Against Staphylococcus Epidermidis ATCC 12228 Bacteria - Nadia Nurul Wachida; Tatiana Siska Wardani; Rahmat Hidayat (International Journal of Health Engineering and Technology, 2026)
Staphylococcus epidermidis is a bacteria that causes mild skin infections accompanied by abscesses, with a high  prevalence in Indonesia, requiring natural alternatives due to antibiotic resistance. This study aimed to evaluated antibacterial activity of 96% ethanol extract and n-hexane, ethyl acetate, water fractions of pineapple peel (Ananas comosus L. Merr.) against S. epidermidis ATCC 12228 and to determined MIC/MBC of the most active fraction. This quantitative and experimental study used the disk diffusion and liquid/solid dilution. methods. Population: pineapple peels from Blitar, East Java; sample: 700 g Simplicia powder. The nstruments included rotary evaporator, incubator, autoklaf, laminar air flow; data were analyzed using the Kruskal-Wallis (SPSS 25). Results showed that extract produced inhibition zones ranging from 5.63–11.43 mm, ethyl acetate fraction 3.80–7.55 mm, water 2.35–6.88 mm, n-hexane was inactive. The MIC and MBC values of the extract were 25%; ethyl acetate fraction MIC and MBC were 50%. Extract, ethyl acetate, and water fractions exhibited antibacterial activity aginst S. epidermidis, with extract being the most effective.